Archaeologies of Hitler's Arctic War : heritage of the Second World War German military presence in Finnish Lapland - Seitsonen, Oula (Material culture and modern conflict, 2021)
"This book discusses the archaeology and heritage of the German military presence in Finnish Lapland during the Second World War, framing this northern, overlooked WWII material legacy from the nearly forgotten Arctic front as 'dark heritage'--a concrete reminder of Finns siding with the Nazis--and as polluting 'war junk' that ruins the 'pristine natural beauty' of Lapland's wilderness. The scholarship herein provides fresh perspectives to contemporary discussions on heritage perception and ownership, indigenous rights, community empowerment, relational ontologies, and the ongoing worldwide refugee crisis"--